1980
DOI: 10.1111/j.1399-0004.1980.tb01357.x
|View full text |Cite
|
Sign up to set email alerts
|

The Wolf‐Hirschhorn syndrome

Abstract: Most cases of Wolf‐Hirschhorn syndrome occurring among children who die during the perinatal period are not diagnosed by morphologists. However, analysis of the morphological data on the Wolf‐Hirschhorn syndrome reveals that association of typical external features and abnormalities of the brain (shortening of the H2 area of Ammon's horn, dystopic dysplastic gyrae in the cerebellum), eyes (colobomata, microphthalmos, retinal dysplasia) and kidneys (bilateral or unilateral agenesis, cystic dysplasia or polycyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…After the first report by Wolf et al (1965), more than 100 cases of 4p deletion were reported. This partial monosomy now constitutes a clinically recognisable syndrome including a typical craniofacial appearance as found in our case (Lazjuk et al 1980). This characteristic facial appearance is associated with a variable number of external and internal fusion defects: scalp defect, coloboma, cleft lip or cleft palate, preauricular dimple, sacral dimple, cryptorchidism and hypospadias.…”
Section: Discussionsupporting
confidence: 68%
“…After the first report by Wolf et al (1965), more than 100 cases of 4p deletion were reported. This partial monosomy now constitutes a clinically recognisable syndrome including a typical craniofacial appearance as found in our case (Lazjuk et al 1980). This characteristic facial appearance is associated with a variable number of external and internal fusion defects: scalp defect, coloboma, cleft lip or cleft palate, preauricular dimple, sacral dimple, cryptorchidism and hypospadias.…”
Section: Discussionsupporting
confidence: 68%
“…CDH is a severe birth defect characterized by defective formation of the diaphragm, lung hypoplasia and pulmonary hypertension. This has been previously described in 13 WHS patients [Lazjuk et al, 1980;Tachdjian et al, 1992;Kobori and Gregory, 1993;Bird et al, 1994;Howe et al, 1996;Del Campo and Delicado, 1997;Sergi et al, 1998;Tapper et al, 2002;van Dooren et al, 2004;Pober et al, 2005;Basgul et al, 2006;Casaccia et al, 2006;Battaglia et al, 2008]. Sporadic cases of complex heart defects in association with WHS have been reported [http://www.ncbi.nlm.nih.gov/bookshelf/ br.fcgi?book¼ gene&part¼whs].…”
Section: To the Editormentioning
confidence: 67%
“…Thlrdly, aberrant configurations of blood vessels and peripheral nerves as well as occasional absence of peripheral nerves, have been described in patients with aneuploidy (Bersu 1976, Bersu & Ramirez-Castro 1977, Lazjuk et al 1980. Patient 9 (trisomy 18) had a retroesophageal right subclavian artery and both internal carotid arteries arose from the first branch of the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital contractures of joints are often seen with the common syndromes of Buchanan et al (1983) trisomy 3 3p-(mosaic) + + + Metaxotou et al (1981) + Verjaal & De Nef (1978) Merrild et al (1981) 4P -4P + + + + + Dunbar et al (1975) Franceschini et al (1970) Schinzel & Schmid (1972) Lazjuk et al (1980 + + + Yunis (1977) trisomy 5 Ohdo et al (1982) 6q + ring 6 + + Robertson et al (1975) Schmid et al (1979) + Moore et al (1973) 7P -7q + t + + Yunis (1977) McPherson et al (1976) Kelly & Rary (1974) chromosomal aneuploidy, such as trisomy 8 (mosaics), trisomies 13 and 18 and the multiple X syndromes (de Grouchy 1977, Bofinger et al 1973. In addition to the cases reported here, a careful review of the literature shows that arthrogryposis or congenital contractures can be seen with almost any chromosomal aneuploidy.…”
mentioning
confidence: 99%